2017
DOI: 10.1038/s41598-017-12252-3
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin inhibits mast cell-mediated allergic inflammation by targeting PI3K/Akt, MAPK, NF-κB and Nrf2/HO-1 pathways

Abstract: Polydatin(PD) shows anti-allergic inflammatory effect, and this study investigated its underlying mechanisms in in vitro and in vivo models. IgE-mediated passive cutaneous anaphylaxis (PCA) and passive systemic anaphylaxis (PSA) models were used to confirm PD effect in vivo. Various signaling pathway proteins in mast cell were examined. RT-PCR, ELISA and western blotting were applied when appropriate. Activity of Lyn and Fyn kinases in vitro was measured using the Kinase Enzyme System. PD dose-dependently redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 54 publications
4
79
0
Order By: Relevance
“…19 Also, the property of PD on Nrf2 activation has been proved in different diseases models but not IVDD. [20][21][22] In this study, we report that PD exerts properties of antisenescence and anti-ECM catabolism in NPCs treated with TNF-α. Further, we discover that PD decreases the ROS production and protects NPCs from mitochondrial dysfunction induced by TNF-α.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…19 Also, the property of PD on Nrf2 activation has been proved in different diseases models but not IVDD. [20][21][22] In this study, we report that PD exerts properties of antisenescence and anti-ECM catabolism in NPCs treated with TNF-α. Further, we discover that PD decreases the ROS production and protects NPCs from mitochondrial dysfunction induced by TNF-α.…”
Section: Introductionmentioning
confidence: 75%
“…Similar to RSV structurally, PD possesses multiple pharmacological properties of antioxidation, anti‐inflammation and antitumour . Also, the property of PD on Nrf2 activation has been proved in different diseases models but not IVDD …”
Section: Introductionmentioning
confidence: 99%
“…Specially, the level of pro-inammatory factor (TNF-a) was strongly reduced by PD, this was in accordance with many other reports. 10,33,34 Besides, the adding of TNF-a counteracted PD-induced NLRP3 inammasome inactivation via enhancing NF-kB pathway. 35 These researches hent that PD may interact with TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Polydatin (3,4 0 ,5-trihydroxystibene-3-b-mono-D-glucoside; PD), is a natural component extracted from perennial herb Polygonum cuspidatum and a traditional Chinese herbal medicine. 10 Previous studies indicated that PD exerted multiple biological activities including anti-inammation and antioxidation. Chen reported that PD attenuated kidney inammation by inhibiting NF-kB/NLRP3 inammasome activation.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Hossen et al has shown that Src and Syk are likely to bridge TLR stimulation with NF‐κB activation. Ye et al has also reported that the possible underlying mechanism of the antiallergic effect exerted by polydatin (PD) in allergic inflammatory diseases demonstrated that these effects of PD seem to depend on direct inhibition of Syk kinase activity and down‐regulation of the NF‐κB signalling pathway. In the light of all these reports together with our findings, it can be claimed that Syk activation seems to be critical not only for NF‐κB activation but also for the modulation of transactivation of this transcription factor.…”
Section: Discussionmentioning
confidence: 99%